65.8k views
5 votes
If f(x) = 3x-2, find f(8) - f(5)

2 Answers

6 votes

Answer:

f(8) - f(5) = 9

Explanation:

So our function is:

f(x) = 3x - 2

Therefore, f(8) becomes:

f(8) = 3(8) - 2 = 24 - 2 = 22

And f(5) is:

f(5) = 3(5) - 2 = 15 - 2 = 13

Finaly, f(8) - f(5) is therefore:

22 - 13 = 9

So f(8) - f(5) = 9

Hope this helps!

User Viktor Khristenko
by
5.6k points
1 vote

Answer:

9

Explanation:

f(8)=3(8)-2=22

f(5)=3(5)-2=13

22-13=9

User Froast
by
6.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.